Arithmetic Operators Introducing Full Swing High Speed Current-Mode BiCMOS Technology - Ghorbannia Delavar, Arash; Navi, Keivan (Mathematical Problems of Computer Science, 2021)
In this paper we present some multiple valued arithmetic operators introducing high-speed current mode circuits. By applying simple and efficient methods we have reduced the number of transistors and power dissipation. Besides we have achieved a significant improvement in terms of speed and chip area. We have eliminated some parts of circuits and simulated their function with other parts, which results in so many improvements already mentioned.